1971
DOI: 10.1073/pnas.68.6.1321
|View full text |Cite
|
Sign up to set email alerts
|

An Adenylic Acid-Rich Sequence in Messenger RNA of HeLa Cells and Its Possible Relationship to Reiterated Sites in DNA

Abstract: Messenger RNA from HeLa cells contains, as part of the polynucleotide chain, RNase-resistant sequences that are labeled by adenosine but not by uridine. Heterogeneous nuclear RNA also contains adenylate-rich RNase-resistant regions, but in lower proportion than messenger RNA. Hybridization to DNA of 32P-labeled messenger RNA reveals that some of the adenylate-rich region is included in the rapidly-hybridizing fraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
111
0

Year Published

1972
1972
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(116 citation statements)
references
References 27 publications
5
111
0
Order By: Relevance
“…A poly(A) polymerase activity was first isolated from calf thymus in 1960 [5], and its role in pre-mRNA 3′-end processing was recognized ten years later [6][7][8]. Subsequent studies showed that the primary RNA transcripts extended beyond the site of polyadenylation, indicating that eukaryotic pre-mRNA 3′-end processing requires both cleavage and polyadenylation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A poly(A) polymerase activity was first isolated from calf thymus in 1960 [5], and its role in pre-mRNA 3′-end processing was recognized ten years later [6][7][8]. Subsequent studies showed that the primary RNA transcripts extended beyond the site of polyadenylation, indicating that eukaryotic pre-mRNA 3′-end processing requires both cleavage and polyadenylation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Polyadenylic Acid Content of the in vitro Synthesized RNA. Most of the eukaryotic messenger RNAs and some of the HnRNA contain poly(A) sequences at their 3' end (21) (7) (8) (9). Marzluff et al (11) have shown that nuclei isolated from mouse myeloma cells are capable of synthesizing poly(A) sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the eukaryotic messenger RNAs and some heterogeneous nuclear RNAs contain polyadenylic acid sequences (7,8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terminal nucleotide sequences of mammalian messenger RNAs have become of particular interest recently due to the finding that untranslated polyadenylic acid linked to the messenger might play a role in the processing of nuclear precursor RNA (1)(2)(3)(4)(5). During infection of suitable cells, the single-stranded RNA of poliovirus serves as template in viral RNA replication and also as mRNA for virus-specific protein synthesis (6).…”
mentioning
confidence: 99%